TQM implementation for enhancement of product and service quality: a review on developments and latest trends - Shailendra Pawanr; Pallab Sarmah; Kapil Gupta (Journal of Applied Research in Technology & Engineering)
Total quality management (TQM) is one of the primary techniques of industrial engineering being applied worldwide. This paper presents a review of important case studies conducted mainly in the last five years on the implementation of TQM for various purposes related to the management of quality in different industrial and service scenarios. It first introduces TQM and discusses its vital aspects, followed by an analysis of selected past work. It ends with a conclusion and future research directions. Essential points of TQM implementation in multiple facilities of industrial and service sectors are highlighted, and the latest trends, such as TQM integration with sustainability and Industry 4.0, are covered. The article not only aims to fill the gap where there is a scarcity of a recent review article analyzing and highlighting the developments and latest trends in TQM implementation for product and service quality enhancement but also to encourage the researchers, scholars, and engineers to conduct research and development in this domain to establish the field further.